The combined stop-loss and quota-share reinsurance: Conditional tail expectation-based optimization from the joint perspective of insurer and reinsurer - Khreshna Syuhada; Arief Hakim; Suci Sari (Risks, 2021)
In the presence of reinsurance, an insurer may effectively reduce its (aggregated) loss by partially ceding such a loss to a reinsurer. Stop-loss and quota-share reinsurance contracts are commonly agreed between these two parties. In this paper, we aim to explore a combination of these contracts. The survival functions of the ceded loss and the retained loss are firstly investigated. Optimizing such a reinsurance design is then carried out from the joint perspective of the insurer and the reinsurer. Specifically, we explicitly derive optimal retentions under a criterion of minimizing a convex combination of conditional tail expectations of the insurer's total loss and the reinsurer's total loss. In addition, an estimation procedure and more explanations on numerical examples are also presented to find their estimated values.
Keywords: 330; conditional tail expectation; optimal retention; reinsurance; survival function